2013
DOI: 10.1016/j.atmosenv.2013.05.016
|View full text |Cite
|
Sign up to set email alerts
|

The impact on human health of car-related air pollution in the UK, 1995–2005

Abstract: We have analysed the impact on human health of emissions produced by the UK car fleet in the years 1995 and 2005. Calculations were based on reported measurements of pollutant concentration, literature values of exposure response coefficients and data for mortality and morbidity. A share was attributed to the car fleet based on emissions data. Although the total distance driven in the UK increased by 16% over this period to 460 billion km, there was a significant fall in engine emissions as increasingly string… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Nitrogen oxides can also produce photochemical smog with HC. The most famous photochemical smog events are the London photochemical smog and Los Angeles photochemical smog events [2]. Carbon dioxide is a greenhouse gas that can raise the Earth's temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen oxides can also produce photochemical smog with HC. The most famous photochemical smog events are the London photochemical smog and Los Angeles photochemical smog events [2]. Carbon dioxide is a greenhouse gas that can raise the Earth's temperature.…”
Section: Introductionmentioning
confidence: 99%
“…93 gasoline as the fuel, and taxis A, C, and D was more than 4 years after the beginning of use, whereas taxi B was less than half a year after use. As was reported, the formaldehyde and other air pollutants would emit from the car decoration materials and the results showed that temperature would influence the organic concentration more obviously than other factors (Jo and Lee, 2002;Mapou et al, 2013;Smith et al, 2013). According to Figure 1, we could find that the formaldehyde concentration in taxi B was far higher than other three cars, so it can be speculated that the formaldehyde concentration inside was influenced by the car-using conditions and car decoration materials.…”
Section: Resultsmentioning
confidence: 66%
“…The negative impact of automotive air pollution on human health has been proven in many research projects, such as for example [17]. In ecological terms, the advantage of ethanol-powered vehicles over conventional ones stems from the possibility of vehicles being partially or completely (E100) powered with a renewable fuel.…”
Section: Ecological Aspects Of Using Ethanol As Motor Fuelmentioning
confidence: 99%